A Rational Triangle Function as a Model for a Conjugate Gradient Optimization Method. - Abbas Al-Bayati; Basim Hassan (Al-Rafidain Journal of Computer Sciences and Mathematics)
This paper presents the development and implementation of a new numberical based on a non-quadratic Triangular rational function model. For solving non-linear optimization problem .The algorithm is implemented in one version, employing exact line search. This version is compared numberically against versions of the CG-method. The results indicate that in general the new algorithm is superior to the previon algorithm.